New porphyrin-based dendrimers with alkene linked fluorenyl antennae for optics. (30th November 2017) - Yao, Dandan; Zhang, Xu; Abid, Seifallah; Shi, Limiao; Blanchard-Desce, Mireille; Mongin, Olivier; Paul, Frédéric; Paul-Roth, Christine O.
Abstract : The biphotonic ( σ 2 ) singlet oxygen generation capability ( Φ Δ ) of new TFP-based photosensitizers peripherally functionalized with various dendrons containing 2-ethynylflorenyl chromophores is reported along with remarkable fluorescence yields ( Φ F ) of up to 17%. Abstract : The design of porphyrin-based dendrimers featuring conjugated dendrons via alkene spacers herein demonstrates their important role in determining linear optical properties, as well as two-photon absorption (PA) and singlet oxygen photosensitising properties. Improvement in these properties compared to those observed for their analogous alkyne spacers makes these molecules appealing for combined 2-photon-based photodynamic therapy (PDT) and imaging.